Nitrate Concentration from the Water around the Floating Cage fish culture area and from the area with no cage, in the DAM Site PLTA Koto Panjang - Erwin David Sianipar; Madju Siagian; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
In floating cage fish culture activities, degradation of feed remain and fish feces will increase the nitrate content in the surrounding area. A research aims to understand the Nitrate concentration in the water from the cage area and from the area that has no cage has been done from July – November 2014. There were 3 stations, in the 200 m upstream of the cage area (S1), in the cage area (S2) and 200 m downstream of the cage area (S3). Samplings were conducted 4 times, once/2 weeks. In each station, water samples were collected from 3 different depths, in the surface; 2 secchi and 4 secchi depths. Parameter measured were pH, nitrate concentration, phosphate concentration, dissolved oxygen, transparency, temperature and depth. Result shown that the concentration of nitrate in the S1 was 0.02 – 0.09 mg/L; in the S2 was 0.07 – 0.28 mg/L; and in the S3 was 0.05 – 0.18 mg/L. The highest concentration indicates that the Koto Panjang Dam can be classified as eutrophic, especially in the area around the cage. Other water quality parameters measured were temperature : 30.60C – 310C; phosphate 0.03 – 0.35 mg/L; transparency 1.98 m – 2.55 m; depth 27 m – 40 m; pH 5 and free CO2 4.66 mg/L – 15.31 mg/L. The values of water quality parameters indicate that the water quality in the Koto Panjang Dam is good and might be able to support the life of aquatic organisms in that area. Keywords: nitrate, PLTA Koto Panjang Dam, Caged Fish Culture, phosphate